Erotisme dalam Novel Nayla Karya Djenar Maesa Ayu - Jayanti, Etrie; Thahar, Harris Effendi; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This article aim to the describe a form of eroticism in the novel Nayla by Djenar Maesa Ayu.The theory used is the is the structural theory with the techniques of content analysis, the inventory data from the text that indicates the attitude of eroticism. Based on data analysis, it is concluded that the different meanings with erotic pornography.But both said it departed from the human libido, eroticism is a reflection of the behavior, circumstances, or the atmosphere, causing the human libido is based on lust.The result of this research indicate a form of eroticism is revealed through discovery and discussion. In the analysis of the researceh findings are novel structures, by describing the intrinsic element contained inÂ  the content of the novel Nayla by Djenar Maesa Ayu.The conclusion is a form of eroticism expressed as founding, intercourse, kiss, play on bed, in the form of sentences of text.